Macromolecules in solution and Brownian relativity - Mezzasalma, Stefano A. (Interface science and technology, 2008)
This book illustrates the recent picture of statistical physics of polymers and polymer solutions that emerges from some paradigms of contemporary science joint together. Among its principal aims are discussing the consequences of a novel self-diffusion theory, which benefits from an extension towards relativistic-like principles, and the generalization of usual concepts met in polymer science in terms of geometry alone. The monograph gives the whole fundamentals necessary to handle the view proposed, which is set in the final chapters. All the formers see about to provide the reader with a comprehensive treatation of the necessary fundamentals of classical, relativistic, quantum and statistical mechanics. Among the most important mechanical theories ever developed, a chapter on the Brownian movement and another on macromolecules prepare the ground that is specific to face universality and scaling behaviors in polymer solutions. The scope of the book is therefore two-fold: On the one hand, it wishes to involve the readers and scholars into a new research on polymer physics and chemistry. On the other, to get close chemical physicists and physical chemists to disciplines which, traditionally, are far from their direct fields of interest. Cross-disciplinarity Novelty Potentiality.